Comparative Evaluation of Microleakage between Three Adhesive Agents - Shiva Jafarnia; Hani Donyavi; Mohammad Erfan Ardestani; Mohammad Moein Azizi; Sima Shahabi (Mashhad University of Medical Sciences, 2022)
Introduction: The aim of this study was to evaluate and compare the microleakage of three adhesives in class V composite restorations. Methods: 30 extracted third molars were divided into three groups based on the adhesive types. Two class V cavities were prepared on each tooth. An individual adhesive was used for bonding in each group and cavities were restored with resin composites. The specimens in each group were aged by thermal cycling and submerged in silver nitrate solution. Microleakage was assessed with a stereo microscope. Statistical analysis was performed to compare the extent of microleakage between the groups. Results: The microleakage of the universal adhesive G-Premio Bond was significantly lower than that of the other two bonding agents. No significant difference was found between G-Premio Bond and Iperbond Ultra (p> 0.99), although the 6th-generation adhesive Quickbond had the highest microleakage compared to the other two. Conclusion: Microleakage was influenced by the type of adhesive. Lower levels of microleakage in the universal adhesives led to longevity and durability of the restoration.